Women, children and adolescents in conflict countries: an assessment of inequalities in intervention coverage and survival - Inácio Crochemore Mohnsam da Silva; Aluísio J D Barros; Nadia Akseer; Ties Boerma; Zulfiqar Ahmed Bhutta; Eran Bendavid; James Wright; Hana Tasic; Karl Everett; Elaine Scudder; Ribka Amsalu; Mahdis Kamali (BMJ Global Health)
Introduction Conflict adversely impacts health and health systems, yet its effect on health inequalities, particularly for women and children, has not been systematically studied. We examined wealth, education and urban/rural residence inequalities for child mortality and essential reproductive, maternal, newborn and child health interventions between conflict and non-conflict low-income and middle-income countries (LMICs).Methods We carried out a time-series multicountry ecological study using data for 137 LMICs between 1990 and 2017, as defined by the 2019 World Bank classification. The data set covers approximately 3.8 million surveyed mothers (15–49 years) and 1.1 million children under 5 years including newborns (<1 month), young children (1–59 months) and school-aged children and adolescents (5–14 years). Outcomes include annual maternal and child mortality rates and coverage (%) of family planning services, 1+antenatal care visit, skilled attendant at birth (SBA), exclusive breast feeding (0–5 months), early initiation of breast feeding (within 1 hour), neonatal protection against tetanus, newborn postnatal care within 2 days, 3 doses of diphtheria, pertussis and tetanus vaccine, measles vaccination, and careseeking for pneumonia and diarrhoea.Results Conflict countries had consistently higher maternal and child mortality rates than non-conflict countries since 1990 and these gaps persist despite rates continually declining for both groups. Access to essential reproductive and maternal health services for poorer, less educated and rural-based families was several folds worse in conflict versus non-conflict countries.Conclusions Inequalities in coverage of reproductive/maternal health and child vaccine interventions are significantly worse in conflict-affected countries. Efforts to protect maternal and child health interventions in conflict settings should target the most disadvantaged families including the poorest, least educated and those living in rural areas.